2016
DOI: 10.1364/oe.24.00a592
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processable organic-inorganic hybrid hole injection layer for high efficiency phosphorescent organic light-emitting diodes

Abstract: PSS-MoO3-based HIL is beneficial for application in solution-processed organic electronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…57,58 Recently, most researchers focused on the polymeric blending strategy to alter the PEDOT:PSS work function to achieve a higher HOMO level. 33,44,59 We herein fabricated the hole-only device with a PVP interlayer and monitored the current density under varied applied forward bias. The hole-only device was fabricated with the control PEDOT:PSS and the PVP interlayer of different thicknesses, following the architecture of the ITO/PEDOT:PSS/PVP interlayer (x)/CsPbBr 3 + 5% PVP/poly-TPD/Ag, where x refers to different concentrations such as 1.0, 1.5, 3.0, and 5.0 mg/mL.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…57,58 Recently, most researchers focused on the polymeric blending strategy to alter the PEDOT:PSS work function to achieve a higher HOMO level. 33,44,59 We herein fabricated the hole-only device with a PVP interlayer and monitored the current density under varied applied forward bias. The hole-only device was fabricated with the control PEDOT:PSS and the PVP interlayer of different thicknesses, following the architecture of the ITO/PEDOT:PSS/PVP interlayer (x)/CsPbBr 3 + 5% PVP/poly-TPD/Ag, where x refers to different concentrations such as 1.0, 1.5, 3.0, and 5.0 mg/mL.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…3232 Rational comparison between evaporated and solution-processed MoO 3 suggested that the surface roughness of the platform contributes to device deterioration. 33 Meng et al addressed PEDOT:PSS luminescence quenching and stability issues using solution-processed MoO 3 -ammoniatreated PEDOT:PSS. 34 Several works were performed with Al 2 O 3 thin films to improve the electron blocking, thereby enhancing the stability of the device; however, the vapor deposition technique is complicated.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another work, Hou et al showed that the insertion of a MoO 3 layer between the ITO and PEDOT:PSS enhances the efficiency of a hybrid perovskite cell, as well [10]. Similarly, Lee et al showed that the power efficiency of OLEDs employing a PEDOT:PSS-MoO 3 composite layer (or a simple MoO 3 layer) on ITO surpasses the one of devices with PEDOT:PSS on ITO [8]. From these illustrative examples, it can be seen that MoO 3 can be combined with-or even replace-PED-OT:PSS, leading to improvements in device performance.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…Depending on their electronic band structure, certain dielectrics are therefore used as electron selective layers and others as hole-selective layers in devices, allowing efficient charge carrier extraction. One of the most widely implemented dielectrics in solar cells and organic light-emitting diodes (OLEDs) is molybdenum trioxide (MoO 3 ) [8][9][10][11][12] whose high work function between 4.7 and 6.9 eV [13][14][15][16] makes it an efficient hole-selective interfacial layer.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%